Treatment of Patients with Chronic Pancreatitis against the Background of Hypothyroidsis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Relevance. The activity of the pancreas (PG) is under the regulatory influence of thyroid hormones[1,3,18]. When the thyroid gland is removed, pancreatic atrophy is observed, and the use of thyroid hormones leads to restoration of pancreatic mass[2,3,19,20]. On the other hand, in patients with acute edematous pancreatitis, 72 hours after hospitalization, a decrease in the level of triiodothyronine, characteristic of hypothyroidism, is shown, but without clinical manifestations of the latter[4,5]. A decrease in the content of triiodothyronine and thyroxine was noted in patients with chronic pancreatitis[6,7,23]. According to the literature data, the close relationship between the thyroid gland and the pancreas is obvious, but the features of the course and treatment of chronic pancreatitis (CP) in patients with hypothyroidism remain insufficiently studied[8,9,10]. In this work, the task is to determine pathogenetically substantiated therapy for patients with CP with concomitant hypothyroidism[21,22,24].